Retrospective study of photodynamic therapy for pulsed dye laser‐resistant port‐wine stains. Issue 4 (3rd February 2020) - Han, Yue; Ying, Hanru; Zhang, Xiaolin; Yu, Wenxin; Cen, Qingqing; Chen, Xuanfeng; Qiu, Yajing; Chen, Hui; Jin, Yunbo; Ma, Gang; Lin, Xiaoxi
Abstract: Pulsed dye laser‐resistant port‐wine stains present a therapeutic challenge. The aim of this study was to evaluate the efficacy and safety of photodynamic therapy for treating these lesions. A total of 67 patients with pulsed dye laser‐resistant cervicofacial port‐wine stains were retrospectively assessed after undergoing photodynamic therapy mediated with a combination of hemoporfin and 532‐nm light. For objective evaluation of photodynamic therapy efficacy, first, the colorimetric changes in the port‐wine stain lesions were evaluated according to the L * a * b * color coordinate system, then the values of color changes (Δ E ) and blanching rate were calculated. For subjective evaluation of improvement, photographs taken before and after photodynamic therapy were evaluated by three independent assessors blindly. Patient satisfaction was also used as a factor in the subjective evaluation. Adverse events were recorded after treatment. The median Δ E decreased significantly from the pretreatment value of 13.42 to 9.90 at the 2‐month follow up ( P < 0.001). The median blanching rate of port‐wine stains was 28.04% after an average of 1.21 sessions of photodynamic therapy. Based on the overall visual assessment, 46.2% patients showed excellent or good levels of improvement (>50% color blanching). Adverse events were minimal, transient and self‐limiting. In conclusion, photodynamic therapy serves as an alternative means to treat pulsed dye laser‐resistant port‐wine stains.